Análise histológica do trato gastrintestinal de avestruzes jovens (Struthio camelus Linnaeus, 1758) - Monteiro, Cristina Maria Rodrigues [UNESP]; de Souza, Nair Trevisan Machado; Carvalho, Roberto Gameiro de [UNESP]; Souza, Wilson Machado de [UNESP] (Universidade Federal de Santa Catarina (UFSC), 2009)
The histological aspects of the gastrointestinal tract of the ostrich (Struthio camelus) have been little studied, so this research is focused on such analysis. To this end, samples were obtained from different segments of the digestive tubes of five young ostriches aged 20 to 30 days. Based on the results, the authors conclude that the different segments of the digestive tube of the young ostrich presents the same general structure as that of other domestic birds and mammals, with some differences that may be due to age, the species involved, or feeding habits. It is hopes that this analysis will contribute to a better understanding of the physiological processes related to the nutrition and management of ostriches during their growth.
Histological analysis of the gastrointestinal tracts of young ostriches (Struthio camelus).